Efforts to Reduce Burnout Study Through E-Counseling During the COVID-19 Pandemic - Rahman, Fuad Aminur (Universitas Mercu Buana Yogyakarta, 2022)
The burnout of study Â during the Covid-19 pandemic has had a huge impact on students at school. Therefore, the emergence of the Covid-19 pandemic outbreak can affect various patterns of human life, especially in the world of education. Especially the behavior of students in schools after the Covid-19 pandemic. Bring up learning boredom or also called burmout study, which is a condition of boredom, fatigue and boredom in learning, causing a sense of reluctance, lethargy, extraordinary fatigue, and a lack of enthusiasm in the learning process, especially during the Covid-19 pandemic. In teaching and learning activities (KBM) during the pandemic, students carry out online learning activities (online). In response to this, an optimal implementation of a guidance and counseling (BK) teacher is needed to reduce this behavior, one of which is through E-Counseling or commonly called electronic (online) counseling services. Counseling services are not only carried out face-to-face in a closed room, but can be carried out through a remote format via a website in the form of an application, so that it can be interpreted as a counseling process that can be used as an alternative by guidance and counseling teachers in reducing burnout study during the pandemic. Based on the results of the implementation of e-counseling activities at SMAN 1 Cihara, it was found that e-counseling had a good impact in reducing burnout study behavior during the Covid-19 pandemic.